Estudo da composição química das carnes de caprinos e ovinos criados no sertão do Ceará - Almeida, Magda Maria Marinho (1990)
Chemical composition of goat and sheep meatfrom the most representative breeds in Northeast Brazil was studied. Goats used in this experiment were undetermined in breed (Sem Raça Definida), and had same age and sex. They were fed similarly except for a mineral phosphate supplement (A = no phosphate; B = bicalcic phosphate; C = rock phosphate). Sheeps from the breed Deslanado Branco de Morada Nova were all similar concerning age, sex and feeding regime. Meat from shoulder and leg from both goat and sheep were analized for proximal composition (moisture, protein, fat and ashes), macro minerals (Ca, Mg, P, Na and K); micro minerals (Fe, Zn, Mn and Cu), as well as for cholesterol and phospholipids. Meats from both types of animals were found to range from 69.15 to 76.65 g/100g for moisture, from 17.60 to 20.90 g/ 100g for protein, from 3.80 to 12.30 g/100g for fat and from 0.85 to 0.95 g/100g for ashes. Shoulder goat meat was higher in fat Zn and Cu contents than leg goat meat. The opposite situation was found for moisture, P and Cu in this typpe of meats. The use of phosphate supplementation in the diets showed no effect on P and Ca content in the meats. Feed containing bicalcic phosphate supplementation, however, produced goat meat with lower levels of Cu and Zn than that containing rock phosphate or no phosphate. Shoulder goat meat showed hig`er levels of cholesterol and phospholipids than leg goat meat. Animals fed with rock phosphate supplementation were found to produce meat with higher levels of cholesterol and phospholipids than those fed with bicalcic phosphate or without phosphate supplementation.